Post activation potentiation of the plantarflexors: Implications of knee angle variations - Gago, P.; Arndt, A.; Ekblom, M. M. (Journal of Human Kinetics, 2017)
Flexing the knee to isolate the single joint soleus from the biarticular gastrocnemius is a strategy for investigating individual plantarflexor`s post activation potentiation (PAP). We investigated the implications of testing plantarflexor PAP at different knee angles and provided indirect quantification of the contribution of gastrocnemius potentiation to the overall plantarflexor enhancements post conditioning. Plantarflexor supramaximal twitches were measured in ten male power athletes before and after a maximal isometric plantarflexion (MVIC) at both flexed and extended knee angles. Mean torque and soleus (SOLRMS) and medial gastrocnemius (MGRMS) activity were measured during the MVIC. The mean torque and MGRMS of the MVIC were lower (by 33.9 and 42.4%, respectively) in the flexed compared to the extended position, with no significant difference in SOLRMS. After the MVIC, twitch peak torque (PT) and the rate of torque development (RTR) potentiated significantly more (by 17.4 and 14.7% respectively) in the extended as compared to the flexed knee position, but only immediately (5 s) after the MVIC. No significant differences were found in the twitch rate of torque development (RTD) potentiation between positions. It was concluded that knee joint configuration should be taken into consideration when comparing studies of plantarflexor PAP. Furthermore, results reflect a rather brief contribution of the gastrocnemius potentiation to the overall plantarflexor twitch enhancements.